Designing Risk Qualitative Assessment on Fiber Optic Instalation Project in Indonesia - Devi Pratami; Fachri Fadlillah; Imam Haryono; Ageak Raporte Bermano (School of Industrial and System Engineering, Telkom University, 2018)
A project always has risks that can lead to project failure. In the project, a risk analysis is required to provide an evaluation for the project to proceed as planned. In the event of inadequate planning and ineffective control, it will result in irregularities identified as a risk to the project. This study aims to analyze the qualitative risk on Fiber Optic Installaion project in Sukabumi, West Java, Indonesia. In addition, risk assessment is undertaken on project implementation. Assessment of risk using the impact and probability to measure the impact of risk occurrence. The impacts are more detailed by classified by time impact, cost impact, quality impact, safety and security impact, proximity. The result is there are 36 risk that may occur and mostly risks are associaated by quality and safety&security impact. Keywords— risk assessment, qualitative analysis, Project, fiber optic.